A Mini Review: Preliminary Study of Bio-Medical Physics on Development of FRRS to Reduce Pain After Heavy Activities - Primasari Cahya Wardhani; Nur Aini Fauziyah; Pardi Sampe Tola; Zakiyah Dania Billah (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Reflexology on the feet is a traditional Chinese medicine (TCM) therapy method. Specifications that must be considered in the manufacture of electrostimulators for acupuncture therapy are waveform, intensity, frequency, and duration of therapy. Scientific studies have confirmed that TCM FB can promote microcirculation, improve skin permeability, and boost drug absorption. Based on data from research collected in the last five years, the method used for foot reflexology is TENS, FES, FNS, and the manufacture of reflexology cotton sandals. By looking at these significant results of the usage of foot stimulator, but it has not been supported by the development of a comprehensive foot reflexology device. Thus, the development of the FRRS device has the potential to become a non-invasive and non- pharmacological therapy device with several advantages in its usage using magnetic electrodes (magnetic plate electrodes), which are very effective at directing the flow of electrical energy to the body through the soles of the feet.